Genome-wide association mapping and stability analysis of root mealiness in cassava (Manihot esculenta Crantz) - Uchendu, U.K. (University of Ghana, 2020)
Cassava breeders have made significant progress in developing new genotypes with improved agronomic characteristics such as improved root yield. However, these new and improved cassava genotypes in cultivation in Nigeria have undergone little or no improvement in their culinary qualities; hence, there is a paucity of information on the texture of boiled cassava roots, particularly with regard to its mealiness. The objectives of this study were to: (i) elicit farmers’ knowledge, perceptions and their preferences for quality attributes in boiled and pounded cassava, (ii) identify genomic regions and polymorphisms associated with natural variation for root mealiness and associated traits in cassava and (iii) assess genotype × environment interaction effects for root mealiness and associated traits in cassava. The participatory rural appraisal (PRA) component of this study was conducted among 360 cassava farmers in Abia, Akwa Ibom and Benue states in Nigeria using semi-structured farmers’ interviews and focus group discussions (FGDs). The PRA revealed that the majority of the farmers were aware of boiled and pounded cassava and had consumed both food forms without encountering health problems. Nonetheless, the two food forms (boiled and pounded cassava) were not often consumed by most farmers in the surveyed states. Variety type was identified as the most important factor affecting the texture of boiled and pounded cassava, followed by age of plant. Socio-economic factors including male farmers (end-users), age, marital status, education and cassava farming experience were observed to have significant positive or negative influence on the consumption of boiled and pounded cassava in the surveyed states. Sweet taste, less starch, softness and low fibre were identified as food quality attributes preferred in boiled cassava by men and women farmers, whereas for pounded cassava, stretchability, smoothness, sweet taste, softness and ease of pounding (form dough easily) were identified as the preferred food quality attributes by men and women farmers across the states surveyed. Most farmers showed willingness and ability to adopt and consume boil-and-eat cassava genotypes when made available to them. The results, therefore, suggest that education of farmers on the nutritional benefits of consuming boiled and pounded cassava through awareness and educational campaigns should be provided. To determine the genetic factors associated with root mealiness and other culinary traits in cassava, a high throughput genotyping-by-sequencing (GBS) platform was used in genotyping an association panel of 142 genotypes using 59,792 single nucleotide polymorphisms (SNPs) distributed across the cassava genome. Through genome-wide association (GWA) analysis, 80 significant SNP markers associated with root mealiness, fibre, adhesiveness, taste, aroma, colour and firmness on chromosomes 18, 17, 13, 10, 6, 5, 4, and 1 were identified. The study further identified relevant candidate genes that are co-located with peak SNPs linked to these traits in cassava. A survey of the cassava reference genome v6.1 positioned the SNPs on chromosome 13 in the vicinity of Manes.13G026900, a gene recognized as being responsible for cell adhesion and for the mealiness or crispness of vegetables and fruits, and also known to play an important role in cooked potato texture. These findings provide valuable insights into understanding the underlying genetic basis of boiled cassava root texture. After validation, the SNPs as well as candidate genes identified in this study could provide important genomic resources for use in marker-assisted selection (MAS) and genomic selection (GS) to accelerate genetic improvement of cassava culinary qualities in West Africa, particularly in Nigeria, where the consumption of boiled and pounded cassava is low. On the effects of genotype × environment interaction (GEI), the study revealed significant influence of genotype, environment and GEI on the performance of genotypes. The AMMI analysis showed that GEI explained the greatest proportion of the treatment sum of squares (SS) for all the traits studied. The genotype plus genotype by environment (GGE) biplot identified genotypes for specific environments for root mealiness, fresh storage root yield and dry matter content. For root mealiness, genotype B1-50 performed best in Igbariam 2018 (E1); NR110512 was the best performing genotype in Umudike 2019 (E6), whereas genotypes NR110213, NR100225 and NR1S1112 were best performers in Otobi 2019 (E4). For fresh storage root yield, genotypes NR110160 and NR110315 were the best performers in Igbariam 2018 (E1) and Igbariam 2019 (E2); genotype NR090088 was the best yielder in Umudike 2018 (E5) and Umudike 2019 (E6), while genotypes NR090176 and NR090001 performed best in Otobi 2019 (E4). NR110348 and NR1S10064 were the most superior genotypes for dry matter content in Igbariam 2019 (E2) and Umudike 2019 (E6); genotypes B1-5, NR100248, NR110160 and TMS051625 performed best in Igbariam 2018 (E1) and Umudike 2018 (E5), whereas genotype NR100216 was the best performer for dry matter content in Otobi 2019 (E4). Low to moderate broad sense heritability values were observed for all traits, except for colour of boiled roots. Broad sense heritability estimate (24%) and genetic advance were low for root mealiness, indicating that the trait appears to be under environmental control, hence progress in selection may be slow and may require recurrent selection overtime to make significant progress. A significant positive relationship was found between root mealiness and fresh storage root yield (r = 0.18, P<0.05), but the relationship was rather weak. In addition, the phenotypic correlations observed among traits were generally low. From this study, five best performing genotypes (B1-50, COB6-4, NR010161, the check variety, TMEB693, and NR110376) were identified for root mealiness and could form potential parents for use in genetic improvement and/or use as potential genotypes for final release to farmers after further evaluation. The results, therefore, showed that multi-environment studies in cassava could help discriminate genotypes with superior performance.